1995
DOI: 10.1089/thy.1995.5.165
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Influence of Thyroglobulin (Tg) Autoantibodies and Other Interfering Factors on the Use of Serum Tg as Tumor Marker in Differentiated Thyroid Carcinoma

Abstract: The purpose of the study was to examine the value of a commercial immunoradiometric (IRMA) method for measuring serum thyroglobulin as a tumor marker after treatment for differentiated thyroid carcinoma. A prospective analysis of consecutive serum samples from 53 patients was performed using the IRMA method and a traditional double antibody radioimmunoassay (RIA). The results were compared with those of 100 healthy control subjects and furthermore the method was validated by investigating sera from 24 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 13 publications
5
15
0
1
Order By: Relevance
“…The exogenous Tg recovery test has been proposed for the detection of TgAb interference (19,20), but, in agreement with other studies (6,9,10,13,14), we demonstrated here that normal recovery of Tg in serum containing TgAb does not exclude interference and this method should therefore not be used for the validation of Tg measurements. This divergence might be explained by differences in endogenous and exogenous Tg, the use of different isoforms with variable immunoreactivity in the preparation of the test (21), and TgAb heterogeneity (22).…”
Section: Discussionsupporting
confidence: 89%
“…The exogenous Tg recovery test has been proposed for the detection of TgAb interference (19,20), but, in agreement with other studies (6,9,10,13,14), we demonstrated here that normal recovery of Tg in serum containing TgAb does not exclude interference and this method should therefore not be used for the validation of Tg measurements. This divergence might be explained by differences in endogenous and exogenous Tg, the use of different isoforms with variable immunoreactivity in the preparation of the test (21), and TgAb heterogeneity (22).…”
Section: Discussionsupporting
confidence: 89%
“…In these patients, a rising Tg level indicates disease that is likely to become clinically apparent (281,283,301,(303)(304)(305). In this setting, routine surveillance is recommended with imaging and treatment determined by the degree of Tg elevation and its trend over time (see Fig.…”
Section: Incorporating Tg Levels Into Clinical Carementioning
confidence: 99%
“…TgAb are detected in up to 20%-25% of patients with DTC, primarily PTC, and they interfere with Tg measurements in a qualitative, quantitative, and method-dependent manner, rendering the Tg level uninterpretable (304,(306)(307)(308)(309)(310). Antibody interference with the most commonly used Tg immunometric assays always results in underestimation of Tg (i.e., a potentially false negative test), whereas interference with radioimmunoassay has the potential to cause either under-or overestimation of Tg, depending on the characteristics of the patient-specific TgAb and the radioimmunoassay reagents (307,310).…”
Section: Children With Tg Autoantibodiesmentioning
confidence: 99%
“…Anti-Tg autoantibodies (TgaAb) were detectable in 10 out of the 21 patients (see Table 1). In the selected sera with TgaAb, TgaAb did not seem to interfere in the Tg RIA insofar as serum dilutions yielded displacement curves parallel to the standard curve (20)(21)(22). Four serum samples were collected from patients with subacute thyroiditis diagnosed on clinical and serological grounds including elevated levels of circulating Tg (200-2900 ng/ml; mean: 1030 ng/ml).…”
Section: Journal Of Endocrinology (1998) 139mentioning
confidence: 99%